An overview of the environmental awareness about waste tires in Paragominas town - PA - Santos, Sara Dorea de Oliveira; Souza, Karinne de Lima; Moreira, Samya de Freitas; Lobo, Ronilson Rosário; Correia Junior, Edesio Ramos; Silva, Túlio Marcus Lima da (Ciência e Natura, 2019)
Waste tires, when they are not properly managed, become a major factor in environmental degradation. The objective of this study was to characterize the knownlegment and environmental consciousness level of establishments that manipulate or deal directely with tires in the town Paragominas – PA, as well as its commitment level with the legislation about the reverse logistics applied to discard of waste. This is an exploratory study, associated to a survey of bibliographic data with a temporal cut for the last 10 years, besides the application of interviews and socioenvironmental forms as data collection procedures. The results indicated that only 3.33% (CI: 0.00-8.71%) of the enterprises have a high-level understanding about the reverse logistics. The numbers were also worrisome in relation to the knowledge of Law No. 12,305:2010, in which 40.00% (CI: 25.33-54.67%) of the companies said they did not know. Despite the lack of normative instructions, 100% of the visited companies showed a desire to take part in reuse projects and/or recycling discarded tires. As a proposal for the problem, it is worth mentioning the application of alternatives that allow the reuse of waste tires in medium-large scale.